Parameter Genetik Jagung Populasi Bisma pada Pemupukan Berbeda. I. Ragam Aditif-Dominan Bobot Biji Jagung - Sutoro Sutoro; Abdul Bari; Subandi Subandi; Sudirman Yahya (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2006)
New maize varieties could be obtained through improvement of their plant populations. The method used in selection in the crop improvement was based on values of their genetic parameters. Bisma is one of the maize varieties that has a broad genetic background. New maize varieties could be obtained by improving their population through selection under different environmental conditions. Genetic parameter value were estimated by conducting an experiment under NCD II crossing at Bogor. Twenty seven sets, which were developed from three females and three males of S1 as parents of each set, were evaluated under three different fertilization schemes. Results of the experiment showed that the additive genetic variance was significantly different from zero, and so among the different levels of fertilizer applications. The dominant variances was not significant under the three different levels of fertilization applications. The additive genetic variance was lower under the low level of fertilizer application than that on the higher level of fertilization application. This might be due to the scale effect. To reduce effect of scale, the data were transformed by dividing the grand mean value. After the data transformation, the genetic variance under the low level of fertilizer application tended to be greater than that under the higher level of fertilizer application. There was a tendency that population improvement of Bisma variety could be achieved better under lower level of fertilizer applications than under the higher ones.